2017
DOI: 10.18488/journal.70.2017.43.77.86
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Rural Youths Participation in Family Farming in Benue State, Nigeria: Implications for Policy

Abstract: Article HistoryThe study was conducted in Benue State, Nigeria to assess prospects of rural youths participation in family farming. Data were collected from a sample of eighty (80) respondents using questionnaire/interview schedule. Frequency, percentage, mean score, standard deviation and factor analysis were used for analyzing data. Majority (75%) of the respondents were males, not married (63.70%), about 99% had formal education, having a mean age of 24 years. Major activities engaged by rural youths in fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Data collected were analyzed using, frequency, percentage, and mean score. [11][12][13][14][15][16][17][18][19][20]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected were analyzed using, frequency, percentage, and mean score. [11][12][13][14][15][16][17][18][19][20]…”
Section: Methodsmentioning
confidence: 99%
“…These conditions have placed the women in a vicious cycle of poverty and are highly disadvantaged in economic empowerment for agricultural development. Agricultural policies on the whole still do not address the needs of rural women farmers adequately (Mbah et al, 2016). Intensifying efforts to improve the cultivation and processing of cassava will improve the lives of many households in Delta State.…”
Section: Introductionmentioning
confidence: 99%
“…Family farmers become the most significant source of employment worldwide, contributing to rural development and food security (Food and Agriculture Organization [FAO], 2018; Mbah, Ezeano, & Odiaka, 2016). Family members could run family farms, a particular enterprise category (Garner & Campos, 2014).…”
Section: And Rural Development Researchmentioning
confidence: 99%
“…The advocacy on youth empowerment is because they are the most critical as agents of change in every society. Besides, most practitioners of agriculture (farmers) were mostly found in rural locations and were deprived of social infrastructures such as schools thus, posing threats to their children's academic career (Mbah et al, 2017;Njeru, 2017;Paisley, 2014). These farmers often adopt some production practices such as excessive use of chemicals for pests, weeds, and disease control; and mechanical land preparation practices, which are unfriendly to the environment (Ogboru and Anga, 2015).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…It was concluded that formal agricultural education had positive impact on youth participation in agriculture. Elsewhere in Nigeria a study was conducted (Mbah et al, 2017) and showed that majority (73.80%) of the respondents had up to secondary education with 11.30% having below secondary school education. The study however indicated as low as 13.80% of youth with tertiary education qualifications.…”
Section: Introductionmentioning
confidence: 99%